Novel ARF/p53-independent senescence pathways in cancer repression - Chan, Chia-Hsin (2011)
Cellular senescence, which can be induced by various stimuli, is a stress response that manifests as irreversible cell cycle arrest. Recent studies have revealed that cellular senescence can serve as a critical barrier for cancer development. Induction of cellular senescence by oncogenic insults, such as Ras over-expression or by inactivation of PTEN tumor suppressor, triggers an ARF/p53-dependent tumor-suppressive effect which can significantly restrict cancer progression. Given the important role of the ARF/p53 pathway in cellular senescence and tumor suppression, drugs that stabilize p53 expression have been developed and tested in clinical trials. However, a major hurdle for p53 targeting in cancer treatment arises from the frequent deficiency or mutation of ARF or p53 in human cancers, which, in turn, profoundly compromises their tumor-suppressive ability. Recent discoveries of novel regulators involved in ARF/p53-independent cellular senescence not only reveal novel paradigms for cellular senescence but also provide alternative approaches for cancer therapy.